Sul commento di Giovanni da Serravalle alla Commedia - Mátyus, Norbert (Verbum – Analecta Neolatina, 2002)
The subject of this article is Giovanni da Serravalle's commentary on Dante's Comedy. The Author argues that Michele Barbi's and Carlo Dionisotti's evaluation of the translation and commentary has to be completed by another point of view: the dependence of Giovanni da Serravalle from other chiosatori on the 14th century. He chooses the interpretation problems of veltro to show this.